National Income, Strategic Discontinuity, and Converging Trajectories of Macroeconomic Policy Initiatives: An Empirical Study of China - Tonn, Victor Lux; Wendian, Chen; C. Li, Hsi (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2018)
The framework of converging trajectories of macroeconomic policy initiatives is employed in the context of strategic discontinuity to study the national income of an advancing economy. A model of systemic changes based upon an equation of production and consumption is presented. In this study of the Chinese economy of 1980-2014, over time, the dynamics of policy imbalance is found to decrease considerably, which is consistent with the decreasing trend of shrinking the differences among the impact coefficients of government consumption, private investment, and private consumption.

Ramy zbieżnych trajektorii inicjatyw polityki makroekonomicznej są stosowane w kontekście strategicznej nieciągłości w badaniu dochodu narodowego rozwijającej się gospodarki. Przedstawiono model zmian systemowych opartych na równaniu produkcji i konsumpcji. W analizie chińskiej gospodarki z lat 1980-2014 z biegiem czasu zauważalna jest znaczna redukcja dynamiki nierównowagi politycznej, co jest zgodne ze spadkową tendencją zmniejszania się różnic pomiędzy współczynnikami wpływu konsumpcji publicznej, inwestycji prywatnych i konsumpcji prywatnej.
Dochód narodowy, strategiczna nieciągłość i zbieżne trajektorie inicjatyw polityki makroekonomicznej: empiryczne badania dotyczące Chin
Keywords: strategic discontinuity; systemic changes; econometric testing; advancing economy; China; nieciągłość strategiczna; zmiany systemowe; testy ekonometryczne; postęp ekonomiczny; Chiny